2012
DOI: 10.1093/jat/bks065
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Determination of Methylphenidate and Ritalinic Acid in Whole Blood from Forensic Cases Using Automated Solid-Phase Extraction and Liquid Chromatography-Tandem Mass Spectrometry

Abstract: A chiral liquid chromatography tandem mass spectrometry (LC-MS-MS) method was developed and validated for quantifying methylphenidate and its major metabolite ritalinic acid in blood from forensic cases. Blood samples were prepared in a fully automated system by protein precipitation followed by solid-phase extraction. The LC-MS-MS method was linear in the range of 0.5 to 500 ng/g for the enantiomers of both analytes. For concentrations above the limit of quantification, coefficients of variation were 15% or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Thomsen et al [29] suggested that a low ratio of dthreoto l-threo-methylphenidate plasma concentration might identify a subject as a poor metabolizer of methylphenidate via CES1. In the present single-dose study, the plasma concentrations of l-threo-methylphenidate were detectable in only five of the twelve subjects and even then in only a minority of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Thomsen et al [29] suggested that a low ratio of dthreoto l-threo-methylphenidate plasma concentration might identify a subject as a poor metabolizer of methylphenidate via CES1. In the present single-dose study, the plasma concentrations of l-threo-methylphenidate were detectable in only five of the twelve subjects and even then in only a minority of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples were prepared using solid‐phase extraction as described for whole blood elsewhere , but without the initial protein precipitation step. Lower limit of quantification was 0.205 ng ml −1 for methylphenidate isomers and 2.05 ng ml −1 for RA isomers.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatographic separation was performed using the same system as described elsewhere . Briefly, a CHIRALPAK ® ‐AGP column (Sigma‐Aldrich, St. Louis, MO) using isocratic elution was employed to separate the enantiomers of both analytes.…”
Section: Methodsmentioning
confidence: 99%
“…MPH is rapidly and extensively metabolized in liver and other tissues by non-microsomal hydrolytic esterases, carboxylesterases (CES) [6–8] to its major and essentially inactive metabolite ritalinic acid (RA) [9]. The half-life of MPH ranges from 2 to 3 h both in adults and in children [10, 11].…”
Section: Introductionmentioning
confidence: 99%